Estimación del impacto ambiental en la cuenca alta de la quebrada la nona y valoración de peligros naturales y antrópicos de su zona de protección en el municipio de Marsella. Risaralda (2021)
The basin of the La Nona stream is of vital importance both hydric and environmental for the municipality of Marsella, its main tributary supplies said municipality and several community aqueducts and hence the interest in carrying out a detailed analysis of its geomorphological characteristics and the environmental impacts present in it. Among the impacts identified were coffee crops, mixed crops, livestock and technical agriculture.